2021
DOI: 10.1161/jaha.120.020196
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 23 and Incident Cardiovascular Disease and Mortality in Middle‐Aged Adults

Abstract: Background Higher circulating fibroblast growth factor 23 (FGF23) associates with greater risk of cardiovascular disease (CVD) and mortality in older adults. The association of FGF23 with cardiovascular outcomes in younger populations has been incompletely explored. Methods and Results We measured C‐terminal FGF23 (cFGF23) and intact FGF23 (iFGF23) in 3151 middle‐aged adults (mean age, 45±4) who participated in the year 20 examination of the CARDIA (Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
0
14
0
3
Order By: Relevance
“…Furthermore, FGF-23, OSM, CCL19, SLAMF1, and HGF consistently showed positive associations with CVD events in PLHIV, both at baseline and during a 5-year follow-up ( Figure S10 ), confirming the well-established link of sustained inflammation in PLHIV under suppressive ART with an increased CVD risk ( Freiberg et al., 2013 ; Nordell et al., 2014 ). Previous studies have highlighted the relation of these proteins with the pathophysiology ( Cai et al., 2014 ; Kubin et al., 2011 ) and the incidence of CVD ( Bell et al., 2016 , 2018 ; Bielinski et al., 2017 ; Ferreira et al., 2019 ; Gruson et al., 2017 ; Ikeda et al., 2021 ; Ix Joachim et al., 2012 ; Paul et al., 2021 ; Vázquez-Sánchez et al., 2021 ) in the general population and PLHIV ( Atta et al., 2016 ; Domingo et al., 2015 ; García-Broncano et al., 2014 ). In addition, OSM receptor has been reported to be associated with the presence of coronary calcium, independent from traditional atherosclerotic CVD risk, in PLHIV on ART ( Kolossváry et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, FGF-23, OSM, CCL19, SLAMF1, and HGF consistently showed positive associations with CVD events in PLHIV, both at baseline and during a 5-year follow-up ( Figure S10 ), confirming the well-established link of sustained inflammation in PLHIV under suppressive ART with an increased CVD risk ( Freiberg et al., 2013 ; Nordell et al., 2014 ). Previous studies have highlighted the relation of these proteins with the pathophysiology ( Cai et al., 2014 ; Kubin et al., 2011 ) and the incidence of CVD ( Bell et al., 2016 , 2018 ; Bielinski et al., 2017 ; Ferreira et al., 2019 ; Gruson et al., 2017 ; Ikeda et al., 2021 ; Ix Joachim et al., 2012 ; Paul et al., 2021 ; Vázquez-Sánchez et al., 2021 ) in the general population and PLHIV ( Atta et al., 2016 ; Domingo et al., 2015 ; García-Broncano et al., 2014 ). In addition, OSM receptor has been reported to be associated with the presence of coronary calcium, independent from traditional atherosclerotic CVD risk, in PLHIV on ART ( Kolossváry et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The categorical analysis revealed that high FGF23 levels were related to increased risk of MI (RR: 1.40, 95%CI:1.03−1.89, p = 0.03; Figure 2A), with low heterogeneity (p = 0.31, I 2 = 2%). Four studies reported continuous analysis (23)(24)(25)(26); the RR of MI Six studies analyzed the relationship between FGF23 levels and stroke (23,24,(27)(28)(29)(30). High FGF23 levels were related to increased risk of stroke in the categorical analysis (RR: 1.20, 95%CI: 1.02−1.43, p = 0.03; Figure 2C), without heterogeneity (p = 0.66, I 2 = 0%).…”
Section: Association Between Fibroblast Growth Factor-23 and Risk Of ...mentioning
confidence: 97%
“…High FGF23 levels were related to increased risk of stroke in the categorical analysis (RR: 1.20, 95%CI: 1.02−1.43, p = 0.03; Figure 2C), without heterogeneity (p = 0.66, I 2 = 0%). In the continuous analysis, the RR of stroke per doubling of FGF23 was 1.21 (95%CI: 0.99−1.48, p = 0.06; Moreover, six studies performed a dose-response analysis (23,24,(27)(28)(29)(30), revealing a non-linear association between FGF23 and stroke (p for non-linearity = 0.10; Figure 3A).…”
Section: Association Between Fibroblast Growth Factor-23 and Risk Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, elevated FGF23 had stronger associations with chronic HF than with atherosclerotic events (including MI, stroke, and peripheral vascular disease) in a prospective cohort of CKD [15], and data from the community-based Framingham Heart Study showed that FGF23 was positively associated with all-cause mortality but not with vascular function or incident cardiovascular disease [16]. A recent study investigating FGF23 and cardiovascular outcomes in a younger (aged 45 ± 4 years) patient cohort with few comorbidities found no associations between FGF23 and incident CAD, CAD events, and mortality, whereas elevated FGF23 was independently associated with a greater risk of hospitalization for HF [17].…”
Section: Introductionmentioning
confidence: 99%